Subtitling Strategy Of Interrogative Sentence In In Time Movie By Genoveva - Styowati, Erna; , Dr. Dwi Haryanti, M. Hum (2016)
SUMMARY Erna Styowati. A 320 120 036. SUBTITLING STRATEGY OF INTERROGATIVE SENTENCE IN IN TIME MOVIE BY GENOVEVA.Research Paper.School of Teacher Training and Education.Muhammadiyah University of Surakarta. 2016. This research focuses on subtitling strategy of interrogative sentence used in the In Time movie subtitler by Genoveva and subtitling quality of In Time movie by Genoveva. This research is descriptive qualitative research. The purposes of this research are: (1) to identify the types and their subtitling strategies of interrogative sentence found in the In Time movie and (2) to describe the subtitling quality of the In Time movie's subtitling. The collected data are analyed based on the theories of subtitling strategies and subtitling quality. The data source are informant and document of the In Time movie's subtitle by Genoveva. The data are utterances containing interrogative sentence found in the data source. The methods of collecting data, the writer uses documentation, questioner and interview. The results of this research show that 1.146 data, firstly the researcher finds 262 data divided into seven strategies of subtitling : (1) 76 data to transfer strategy, (2) 29 data to paraphrase strategy, (3) 45 data of condensation strategy, (4) 10 data to decimation strategy, (5) 15 data to imitation strategy, (6) 1 data to transcription strategy, (7) 86 data to deletion strategy. Secondly there are three aspects for good quality that subtitling should fulfill: accuracy, acceptability, and readability. (1) 881 data or 77% accurately, (2) 253 data or 22% less accurately, (3) 12 data or 1% inaccurately, (4) 776 data or 67.7% acceptability, (5) 370 data or 32.3 % less acceptability, (6) 1047 data or 91.4 % high readability level, (7) 99 data or 8.6 % moderate readability level. Keywords: Interrogative sentence, quality, strategy, subtitling